Cafe society - Tjora, Aksel; Scambler, Graham, 1948- (Palgrave Macmillan, 2013)
While tracing the historical emergence of the caf(r) as a social institution and noting its multiple faces and functions in the modernity of the occident, three themes run like threads of varying texture through the chapters: the social connectivity and inclusion of caf(r)s, caf(r) as surrogate office, and caf(r) as site of exchange for news and views.